(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
Consumer satisfaction is the main target for every company to be able to survive in the midst of very tight competition. The purpose of this study was to determine the effect of product quality, price and service quality on customer satisfaction at Hidden Garden Agro Cafe Baturiti Tabanan Bali, both racially and simultaneously. The population in this study were all consumers of Hidden Garden Agro Cafe Baturiti Tabanan Bali with 100 respondents using accidental sampling method. The data analysis technique used multiple linear regression analysis. Based on the results of the analysis, it was found that product quality, price and service quality had a positive and significant effect on customer satisfaction at Hidden Garden Agro Cafe Baturiti Tabanan Bali, both racially and simultaneously. The suggestion in this research is that companies implement strategies to ensure customer satisfaction by looking at the factors of product quality, price, and service quality.